2014
DOI: 10.1074/jbc.m113.507665
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Calcium Modulates Actions of Orthosteric and Allosteric Ligands on Metabotropic Glutamate Receptor 1α

Abstract: Background: Extracellular Ca 2ϩ alters mGluR1␣ activity but by an unknown mechanism. Results: Mutations in predicted Ca 2ϩ -binding sites modulated the potency of both orthosteric and allosteric modulators. Conclusion: Ca 2ϩ binding exerts multiple types of effects on mGluR1␣. Significance: Improved knowledge of the mechanisms underlying the actions of Ca 2ϩ on mGluR1␣ activity could facilitate development of isoform-selective drugs and/or suggest ways to tune the actions of available drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 54 publications
0
28
0
Order By: Relevance
“…In particular, the modulation of mGlu1 by Ca 2+ has been extensively studied (14,(50)(51)(52)(53)(54), and several sites for divalent cations have been predicted (11,12,55) based on crystal structures of the extracellular domains of mGlu1, mGlu5, and mGlu7 (13,56,57). The first evidence for Cl 2 dependency of ligand binding was provided by Eriksen and Thomsen (16), who showed that this anion increased the binding of the radiolabeled agonist L-AP4 on mGlu4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the modulation of mGlu1 by Ca 2+ has been extensively studied (14,(50)(51)(52)(53)(54), and several sites for divalent cations have been predicted (11,12,55) based on crystal structures of the extracellular domains of mGlu1, mGlu5, and mGlu7 (13,56,57). The first evidence for Cl 2 dependency of ligand binding was provided by Eriksen and Thomsen (16), who showed that this anion increased the binding of the radiolabeled agonist L-AP4 on mGlu4.…”
Section: Discussionmentioning
confidence: 99%
“…Structurally, these receptors are composed of 3 juxtaposed domains: a core 7 transmembrane-spanning domain, common to all GPCRs, is linked via a rigid cysteine-rich domain to the Venus flytrap (VFT), a large bilobed extracellular domain where glutamate binds (10). Besides the well-documented regulation of mGluRs by extracellular calcium (Ca 2+ ) and gadolinium (Gd 3+ ) (11)(12)(13), several studies have pointed to the Cl 2 dependence of glutamate binding on mGluRs (14)(15)(16)(17). However, the molecular basis and the putative physiopathologic relevance of this dependence remain unknown.…”
mentioning
confidence: 99%
“…While group I [mGlu1 and mGlu5 (IUPHAR 5 mGlu 1 and mGlu 5 )] receptors are G q -coupled, group II [mGlu2 and mGlu3 (IUPHAR 5 mGlu 2 and mGlu 3 )] receptors and group III [mGlu4, mGlu6, mGlu7, and mGlu8 (IUPHAR 5 mGlu 4 , mGlu 6 , mGlu 7 , and mGlu 8 )] receptors are G i/o -coupled (Conn and Pin, 1997;Alexander et al, 2013). While the literature is consistent regarding calcium-mediated modulation of mGlu1 receptors (Saunders et al, 1998;Jiang et al, 2014), the contribution of ions to group II and III mGlu receptor signaling is less clear. For example, one study concluded that mGlu3 receptors are activated by calcium (Kubo et al, 1998), while another study claims that ZnCl 2 , not calcium, affects radioligand binding at mGlu2, but not mGlu3, receptors (Schweitzer et al, 2000).…”
Section: Introductionmentioning
confidence: 87%
“…While endogenous cations participate in propagating action potentials, they can also directly modulate receptor activity. For example, calcium flux through N-methyl-D-aspartate receptors influences neuronal depolarization (Traynelis et al, 2010), modulates metabotropic glutamate (mGlu) 1 receptor activation (Jiang et al, 2014), and activates the Ca 12 -sensing receptor (Brown et al, 1993). In contrast, the elemental anion chloride is generally considered an essential but passive participant in neuronal excitability, and to our knowledge it has never been shown to function as an agonist of any receptor in its own right.…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggests that mGluR1 is modulated by extracellular Ca 2+ [141] , and interacts with CaM, and binding of CaM may be inhibited by PKC phosphorylation of mGluR5 [142] and mGLuR7 [143] . Moreover, chronic Pb 2+ exposure appears to reduce mRNA expression of both PKC and CaM in the hippocampus [144] .…”
Section: Mglur1mentioning
confidence: 99%